Towards applying the essential public health functions for building health systems resilience: A renewed list and key enablers for operationalization - Yu Zhang; Geraldine McDarby; Redda Seifeldin; Saqif Mustafa; Suraya Dalil; Gerard Schmets; Natasha Azzopardi-Muscat; James Fitzgerald; Awad Mataria; Ernesto Bascolo; Sohel Saikat (Frontiers Media S.A., 2023)
The COVID-19 pandemic, climate change-related events, protracted conflicts, economic stressors and other health challenges, call for strong public health orientation and leadership in health system strengthening and policies. Applying the essential public health functions (EPHFs) represents a holistic operational approach to public health, which is considered to be an integrated, sustainable, and cost-effective means for supporting universal health coverage, health security and improved population health and wellbeing. As a core component of the Primary Health Care (PHC) Operational Framework, EPHFs also support the continuum of health services from health promotion and protection, disease prevention to treatment, rehabilitation, and palliative services. Comprehensive delivery of EPHFs through PHC-oriented health systems with multisectoral participation is therefore vital to meet population health needs, tackle public health threats and build resilience. In this perspective, we present a renewed EPHF list consisting of twelve functions as a reference to foster country-level operationalisation, based on available authoritative lists and global practices. EPHFs are presented as a conceptual bridge between prevailing siloed efforts in health systems and allied sectors. We also highlight key enablers to support effective implementation of EPHFs, including high-level political commitment, clear national structures for institutional stewardship on EPHFs, multisectoral accountability and systematic assessment. As countries seek to transform health systems in the context of recovery from COVID-19 and other public health emergencies, the renewed EPHF list and enablers can inform public health reform, PHC strengthening, and more integrated recovery efforts to build resilient health systems capable of managing complex health challenges for all people.